Heat exchange processes in thermal installations (quality of heat carrier) - Shynkarenko, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
The operation of boiler equipment is adversely affected by the need to decentralize heat supply systems, unauthorized withdrawal of coolant, switching to low-temperature operation without updating equipment, reducing boiler capacity due to low gas pressure, violation of operating modes and repair schedules, scale deposition on heat exchange surfaces, increased electricity consumption, physical and moral wear and tear of auxiliary equipment and heating networks. These factors lead to chemical incomplete combustion of fuel and its irrational use, corrosion and premature failure of equipment, reduced quality of heat supply and justified consumer complaints. This situation requires immediate modernization of the heat generation and distribution system, as well as the use of low-cost measures to increase the service life of existing equipment.
Keywords: heat exchange; boilers; heat carriers; methodology; supply systems